Making Human Rights a Reality - Hafner-Burton, Emilie (Princeton Oxford Princeton University press, 2013)
In the last six decades, one of the most striking developments in international law is the emergence of a massive body of legal norms and procedures aimed at protecting human rights. In many countries, though, there is little relationship between international law and the actual protection of human rights on the ground. Making Human Rights a Reality takes a fresh look at why it's been so hard for international law to have much impact in parts of the world where human rights are most at risk. Emilie Hafner-Burton argues that more progress is possible if human rights promoters.
Pt. 1. The calculus of abuse -- pt. 2. International law -- pt. 3. A stewardship strategy.
Includes bibliographical references (pages 199-265) and index.
Includes bibliographical references and index.
Specialized.
English.
Keywords: Human rights; Droits de l'homme (Droit international); Human rights